Monuments and Territory: War Memorials in Russian-Occupied Ukraine - Gabowitsch, Mischa; Homanyuk, Mykola (Memory, Heritage and Public History in Central and Eastern Europe, 2025)
Gabowitsch and Homanyuk draw on unique sources to trace the logic of Russian monument policies in occupied Ukraine: wartime on-site ethnography complemented by systematic real-time data collection from online sources, many of which have since disappeared. The book shows how Russian invaders believed their own propaganda about Soviet war memorials being mistreated in Ukraine, and what they did when they discovered well-maintained monuments on the ground. More generally, it also discusses the link between monuments and territorial claims by irredentist empires. Anhand einzigartiger Quellen zeichnet dieses Buch die Logik der russischen Denkmalpolitik in der besetzten Ukraine nach: ethnographische Beobachtungen in der Besatzungszone wurden ergänzt durch die Analyse von Online-Quellen, von denen viele inzwischen verschwunden sind. Die russischen Invasoren glaubten ihre eigene Propaganda über die Zerstörung sowjetischer Kriegsdenkmäler durch die Ukraine; das Buch zeigt, was sie taten, als sie vor Ort auf gut erhaltene Denkmäler stießen. Russlands Umgang mit Kriegsdenkmälern in der Ukraine dient hier als Fallstudie zum Zusammenhang zwischen Denkmälern und imperialen Gebietsansprüchen.